24-Hour Levodopa-Carbidopa Intestinal Gel: Clinical Experience and Practical Recommendations - Thakkar, Sandeep (CNS Drugs, 2021)
Infusion of levodopa-carbidopa intestinal gel (LCIG; also designated carbidopa-levodopa enteral suspension) for 16 hours is a standard treatment for patients with advanced Parkinson’s disease, and clinical observations suggest that 24-hour LCIG infusion may further reduce symptoms. This review provides practical advice on the management of patients transitioning to 24-hour LCIG infusion. We review available clinical data for 24-hour infusion and discuss adjustments to dosing, recommendations for monitoring, and management of patient concerns, based on our clinical experience. Data from multiple studies suggest that LCIG may improve non-motor symptoms. Although few studies have examined 24-hour LCIG infusion, available data indicate that certain patients may benefit from around-the-clock treatment. Studies of 24-hour LCIG infusion are limited by small sample sizes and open-label study designs, which may hamper translation to clinical practice. In our experience, we have found that patients may benefit from 24-hour infusion when reductions in nocturnal symptoms and improvements to quality of sleep are needed. Levodopa-unresponsive freezing of gait or poorly controlled troublesome dyskinesias may also indicate a patient may benefit from 24-hour infusion. Dose adjustments, especially of the nocturnal rate, are typically necessary and, as with 16-hour infusion, patients should be monitored for autonomic dysfunction; overnight wearing off symptoms; weight changes; fluctuations in plasma levels of vitamins B(6)/B(12), folate, and homocysteine; changes in sleep patterns; or worsening of hallucinations, delusions, and/or nightmares. Available data and our clinical experience suggest that 24-hour LCIG may be warranted among selected patients who have poorly controlled nocturnal fluctuations or early morning “off” symptoms.